2003
DOI: 10.1029/2001jd001428
|View full text |Cite
|
Sign up to set email alerts
|

An estimate of the stratospheric contribution to springtime tropospheric ozone maxima using TOPSE measurements and beryllium‐7 simulations

Abstract: [1] Measurements of tropospheric ozone (O 3 ) between 30°N and 70°N show springtime maxima at remote locations. The contribution of seasonal changes in stratospheretroposphere exchange (STE) to these maxima was investigated using measurements from the Tropospheric Ozone Production about the Spring Equinox Experiment (TOPSE) campaign and the beryllium-7 ( 7 Be) distribution from a calculation driven by fields from the Goddard Earth Observing System Data Assimilation System (GEOS DAS).Comparison with TOPSE meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 61 publications
4
42
0
Order By: Relevance
“…This feature was observed on all three flights during spring and thus seems not to be an individual outlier. Furthermore, in the time from April to July stratospheric mass transport into the upper and mid-troposphere is known to occur regularly (Appenzeller and Holten, 1996;Allen et al, 2003;Zanis et al, 2003;Olsen et al, 2004;Schoeberl, 2004). Moreover, Sprenger et al (2003) and Sprenger and Wernli (2003) demonstrated that cross-tropopause mass flux is highest in the midlatitudes where these mercury profiles were measured.…”
Section: North Americamentioning
confidence: 95%
“…This feature was observed on all three flights during spring and thus seems not to be an individual outlier. Furthermore, in the time from April to July stratospheric mass transport into the upper and mid-troposphere is known to occur regularly (Appenzeller and Holten, 1996;Allen et al, 2003;Zanis et al, 2003;Olsen et al, 2004;Schoeberl, 2004). Moreover, Sprenger et al (2003) and Sprenger and Wernli (2003) demonstrated that cross-tropopause mass flux is highest in the midlatitudes where these mercury profiles were measured.…”
Section: North Americamentioning
confidence: 95%
“…However, the overall importance of stratospheric ozone intrusions to the tropospheric ozone budget depends on their distribution with geography and season, and on the fate of the exchanged air parcels, particularly their vertical penetration and residence time Cooper et al, 2004;Thompson et al 2007;Tarasick and Slater, 2008). For these reasons, at least in part, observational estimates of the stratospheric contribution vary widely (e.g., Bachmeier et al, 1994;Browell et al, 1994Browell et al, , 2003Mauzerall et al, 1996;Dibb et al, , 1997Dibb et al, , 2003Allen et al, 2003;Bazhanov and Rodhe, 1997;Elbern et al, 1997;Li et al, 2002;Cooper et al, 2006;Thompson et al 2007).…”
Section: For the Baqs-metmentioning
confidence: 99%
“…Budget analyses performed by Zhang et al [2003] showed that lightning contributes more than 50% of the upper tropospheric NO x over the United States from April to November, impacting the upper tropospheric O 3 budget by as much as 30%. Combined measurement and modeling studies performed by Cooper et al [2006Cooper et al [ , 2007 [Jacob, 1999;Martin et al, 2000], and (c) isentropic cross-tropopause transport of O 3 from the stratosphere [Allen et al, 2003;Jing et al, 2005].…”
mentioning
confidence: 99%